Reverse-engineering method for XPCS studies of non-equilibrium dynamics. (2022) - Ragulskaya, Anastasia; Starostin, Vladimir; Begam, Nafisa; Girelli, Anita; Rahmann, Hendrik; Reiser, Mario; Westermeier, Fabian; Sprung, Michael; Zhang, Fajun; Guttb, Christian; Schreiber, Frank
No abstract available